Innovative Packaging Design: Enhancing the Takeaway Tea Experience at TWG Tea in Plaza Senayan, Indonesia - Erlyana, Yana; Hanifah, Regina Dewi (JIEMS (Journal of Industrial Engineering and Management Systems), 2024)
This qualitative research study explores an innovative packaging design implemented by TWG Tea at Plaza Senayan, Indonesia, to enhance the to-go tea experience. The research focus is mainly on aspects of visual communication, material composition and sustainable properties of packaging. Through extensive observation and analysis of the packaging, the research revealed a visually appealing design featuring vibrant, bold color tones that reflect TWG Tea's distinctive brand identity. The packaging is carefully crafted from 100% biodegradable materials, highlighting the company's commitment to environmental sustainability. The integration of innovative elements such as interactivity and unique opening mechanisms contributes to the functionality and aesthetics of the packaging. The results highlight the important role packaging design plays in capturing consumer attention and communicating brand values. Innovative packaging design enhances the overall tea experience and creates a memorable and immersive journey for customers. By focusing on sustainability principles and using visually appealing elements, TWG Tea successfully differentiates itself in the market and engages consumers on both sensory and ecological levels. The research provides valuable insights for packaging designers and companies looking to enhance the to-go tea experience through innovative packaging solutions.